TI_GERICHTE 52.2025.77 vom 21. Februar 2025 , Commesse pubbliche. Modalità di inoltro delle offerte. Esclusione ingiustificata - TI Tribunale d'appello (2025)
Commesse pubbliche. Modalità di inoltro delle offerte. Esclusione ingiustificata